Analysis of Three Commonly Used Tibia Length Measurement Techniques. Issue 1 (12th July 2018) - Lynch, Jeffrey James; Maijanen, Heli; Prescher, Andreas
Abstract: This study analyzes three tibia length measurement techniques on a sample of 107 tibiae. Two of the techniques meet published criteria by resting the tibia on its posterior surface with the longitudinal axis parallel to an osteometric board. The third technique does not adequately keep the longitudinal axis parallel to the board. Statistical analyses show low levels of interobserver error for all techniques and statistically significant differences between the third technique and the other two techniques. Results report a maximum difference of 6 mm between measurement techniques with the third technique having greater than 95% directional bias. A survey sent out to the American Academy of Forensic Sciences forensic anthropology community reported more than 50% of respondents having been taught the third technique when an osteometric board with a slot/hole is not available. The intermixing of the third technique with the other two has likely contributed to higher levels of interobserver error in tibia length measurements.